Efforts to improve learning outcomes of Indonesian language through participatory method in SMP Negeri 266 Jakarta - Nurhayati Nurhayati (Universitas Indraprasta PGRI, 2017)
This research was being done in Grade VII-A SMP 266 Jakarta with total students is 36 , it was conducted on January – June 2015. The method used in this Action Research by Stephen Kemmis and Robin McTaggart model. It consists of two cycles and each cyclehasthree meetings, and every meeting has four components; Planning, Action Research, Observation and Reflection. The instrument is a questionnaire. In The first cycle, the students made a group in random,the teacher gave assignment in writing a poem. The result was; some student still talked to each other. Yet, on the next cycle the students had to present their job so that they are more interested and tried to finish the job with their group seriously. The average score in the first cycle is 72.61 and the second cycle is improving to 82.86. The result of the observation shows that the learning method with cooperative Participatory method can improve the students learning outcomes